Ibn Taymiya y el Estado Islámico (Dā ʿeš): una aproximación a doctrinas opuestas - Medina Gutiérrez, Felipe (El Colegio de México, 2025)
Many media reports and analysis have claimed that one of the greatest sources of inspiration of the Islamic State is the controversial medieval Muslim thinker Ibn Taymiyya (1263–1328), who is said to have been its “spiritual father”. This text, however, points out the great differences between them. The aim is to deepen the discussion through an analysis of the historical context, followed by a comparative exercise in certain ideological breakpoints. The analysis shows that the Islamic State was not inspired by Ibn Taymiyya in the areas evaluated. Ultimately, this work aims to contribute to the search for a better understanding of the origin and the context of integrist armed groups in the Middle East and the Islamic world.